HUBUNGAN USIA IBU BERSALIN DAN PREEKLAMPSIA KEHAMILAN DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH DI RUANG KEBIDANAN RUMAH SAKIT UMUM DAERAH BOBBAZAR, SKM KALIANDA - Wynne Ardelia Talitha; Sumiyati Sumiyati; Islamiyati Islamiyati (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2017)
Indonesia as a developing country still has a high Infant Mortality Rate (IMR). One of IMR contributors is Low Birth Weight (LBW). The incidence of LBW in Bob Bazar SKM Regional Hospital in 2015 was 15.6%. This number increased from the previous 2 years incidence of 12.9% and 15.2%. The purpose of this study was to determine maternal age relation and preeclampsia pregnancy with LBW incidence in Bob Bazar SKM General Hospital Kalianda Lampung Selatan.This research method uses quantitative research type, with cross sectional design. The population used in this study were all mothers in Bob Bazar District Hospital, SKM Kalianda from January to December of 2016 with 533 people. Samples in this study is 232 samples taken by simple random sampling by drawing. The data collection tool is the check list. Data analysis used univariate analysis in the form of proportion of each variable and bivariate analysis with chi square test. The result of the study showed that the proportion of LBW was 40,1%, the proportion of maternal age was 37,9% and the proportion of preeclampsia 31%. The result of analysis between maternal age and the incidence of Low Birth Weight obtained p-value 0,007 α 0,05 and preeclampsia with the occurrence of LBW obtained p-value 0,018 α 0,05. The conclusions shows that there is a relationship between maternal age and pregnancy preeclampsia with LBW incidence in Bob Bazar SKM General Hospital, Kalianda in 2016.